"I love my ECPs": challenges to bridging emergency contraceptive users to more effective contraceptive methods in Ghana. Issue 3 (17th April 2011) - L'Engle, Kelly Ladin; Hinson, Laura; Chin-Quee, Dawn
Abstract : Background and methods: Emergency contraceptive pills (ECPs) are becoming more popular, yet little is known about the contraceptive preferences of women who take ECPs. Women purchasing ECPs were recruited from pharmacies in Accra, Ghana. A total of 24 semi-structured, qualitative interviews were conducted in May 2008. Results: Nearly all participants preferred ECPs to other contraceptive methods. Although fear of side effects from oral contraceptive pills (OCPs), intrauterine devices and injectables were deterrents to use of those methods, side effects from ECPs were acceptable to this small and highly self-selected group of ECP users. Participants had little knowledge about how other contraceptive methods work and expressed a strong distrust and dislike of condoms. Discussion and conclusion: Study participants loved their ECPs, despite minor discomforts like bleeding, and most had no concerns about repeated use, though these findings may not apply to women outside Accra or women who obtain ECPs from non-pharmacy settings. Future interventions should work to dispel myths about OCPs, condoms and other modern methods, and focus on basic contraception education.